RELATIONSHIP BETWEEN ORAL AND DENTAL HEALTH MAINTENANCE AND THE INCIDENCE OF PERIODONTITIS IN DIABETES MELLITUS PATIENS IN THE WORKING AREA OF UPTD PUSKESMAS (PUBLIC HEALTH CENTER) PAGUAT - Desnawati Otoluwa; Ita Sulistiani; Sitti Fatimah Meylandari Arsad (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Periodontitis is a condition that can occur in diabetes mellitus patiens and is associated with poor maintenance of oral and dental health. This research aims to examine the relationship between oral and dental health maintenance and the incidence of periodontitis in diabetes mellitus patiens. The research employs an analytical observational method with a retrospective design. The sample was selected using a purposive sampling technique. Data were collected using instruments measuring oral and dental health maintenance and a doctor’s diagnosis to determine the presence of periodontitis. Analisis was conducted using the Fisher exact Test (p-value = 0,000). The results indicate a significant relationship between oral and dental health maintenance and the incidence of periodontitis in diabetes mellitus patients. Healthcare workers play a crucial role in educating on the importance of maintaining oral and dental health, including brushing teeth twice daily (morning after meals and before sleeping) and regularly visiting the dentist every six months.